2013
DOI: 10.17221/509/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Changes of antioxidant activity in honey after heat treatment

Abstract: AbstractŠarić G., Marković K., Vukičević D., Lež E., Hruškar M., Vahčić N. (2013): Changes of antioxidant activity in honey after heat treatment. Czech J. Food Sci., 31: 601-606.We determined how the antioxidant activity and total phenolic content of honey changed after being subjected to a high temperature. Antioxidant activity was determined using two methods -FRAP (ferric reducing antioxidant power) and DPPH (1,1-diphenyl-2-picrylhydrazyl) assays. Total phenolic content was determined by modified FolinCioca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 24 publications
5
7
0
1
Order By: Relevance
“…All bioactive compounds of the CPE obtained from the CP dried at 90 °C (CPE90) were higher than those of the freeze dried (CPEFD) and the CP dried samples at the other temperatures, respectively. These may due to the oxidative and hydrolytic enzymes responsible for the bioactive compounds losses during drying are deactivated at the temperature, hence the bioactive compounds preserved (Wojdylo et al, 2007;Šarić et al, 2013). These results are consistent with Punbusayakul and Setha (2014) reported that using higher temperature could preserve the bioactive compounds in the CPE.…”
Section: Results and Discussion Bioactive Compounds Of Cpesupporting
confidence: 66%
See 1 more Smart Citation
“…All bioactive compounds of the CPE obtained from the CP dried at 90 °C (CPE90) were higher than those of the freeze dried (CPEFD) and the CP dried samples at the other temperatures, respectively. These may due to the oxidative and hydrolytic enzymes responsible for the bioactive compounds losses during drying are deactivated at the temperature, hence the bioactive compounds preserved (Wojdylo et al, 2007;Šarić et al, 2013). These results are consistent with Punbusayakul and Setha (2014) reported that using higher temperature could preserve the bioactive compounds in the CPE.…”
Section: Results and Discussion Bioactive Compounds Of Cpesupporting
confidence: 66%
“…These results are consistent with the bioactive compounds of the CPE which suggested that exposure of the CP to the higher temperature is able to preserve the bioactivity of the CPE. The lower temperature might allow the enzymes to convert the active compounds to some other inactive derivatives before the enzymes have been inactivated or some compounds might be converted to the more active compounds as a result of the higher temperature exposure (Wojdylo et al, 2007;Šarić et al, 2013). Table 3 shows that the antimicrobial activity of the CPE from all treatments against all the tested microorganisms, except E. coli TISTR 780 and S. aureus TISTR 1466, showed no significant difference (p > 0.05).…”
Section: Antioxidant Activity Of Cpementioning
confidence: 99%
“…The higher pH value measured in the samples from the Zlatibor region (pH 4.31) was in agreement with the values reported for Slovenian multifloral honeys collected from three regions: Alpine, Pannonian and Mediterranean. 5,8,20,21 The free acidity did not show fluctuations among the studied regions and was in agreement with data reported for neighboring countries. 5,8,20,21 The free acidity did not show fluctuations among the studied regions and was in agreement with data reported for neighboring countries.…”
Section: Resultssupporting
confidence: 91%
“…8 Furthermore, the electrical conductivity was higher in the honey collected from the Zlatibor area (0.74 mS cm -1 ) compared to the samples from the rest of Serbia, as well as from 1880 LAZAREVIĆ et al the values reported for multifloral honeys in other studies. 8,20,21 The optical rotation of the samples coming from Serbia was similar to the data reported for Slovenian multifloral honeys, except for the samples collected from the Zlatibor region, which had lower values. 8,20,21 The optical rotation of the samples coming from Serbia was similar to the data reported for Slovenian multifloral honeys, except for the samples collected from the Zlatibor region, which had lower values.…”
Section: Resultssupporting
confidence: 81%
“…Evidence that thermal treatment of honey did not produce uniform effects on antioxidant capacity of honeys was also reported by other researchers [Turkmen et al, 2006;Šarić et al, 2013]. It has to be appreciated that heat-treatment of honey accelerated the global reduction-oxidation pathways, and several products of the Maillard reaction could contribute to the antioxidant capacities, in addition to polyphenols.…”
Section: Changes In Antioxidant Capacitiesmentioning
confidence: 63%